2022
DOI: 10.3390/electronics11030332
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Improvement of Surface Plasmon Resonance Biosensors with GeS-Metal Layers

Abstract: Surface plasmon resonance (SPR) biosensors, with germanium sulfide (GeS) as a sensitive medium and Al/Ag/Au as the metal layers, are reported as we aim to improve the sensitivities of the biosensors. The sensitivities in conventional SPR biosensors, consisting of only metal Al, Ag, and Au layers, are 111°/RIU, 117°/RIU, 139°/RIU, respectively. Additionally, these sensitivities of the SPR biosensors based on the GeS-Al, GeS-Ag, and GeS-Au layers have an obvious improvement, resultant of 320°/RIU, 295°/RIU, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…demonstrated that the GeS monolayer possesses significantly higher carrier mobility (3680 cm 2 V −1 ) than MoS 2 monolayers [127] . Sensor studies indicate the highest sensitivities for GeS−Al, GeS−Ag, and GeS−Au films at 320 deg/RIU, 295 deg/RIU, and 260 deg/RIU, respectively, surpassing conventional SPR sensors based on Al/Ag/Au films at 111 deg/RIU, 117 deg/RIU, and 139 deg/RIU, respectively [128] . A study executed by Zhao [34] illustrates a substantial advancement in sensitivity for RI detection, achieving an optimized sensitivity of 3581.2 nm / RIU and a figure of merit of 14.37 RIU −1 .…”
Section: Plasmonic Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…demonstrated that the GeS monolayer possesses significantly higher carrier mobility (3680 cm 2 V −1 ) than MoS 2 monolayers [127] . Sensor studies indicate the highest sensitivities for GeS−Al, GeS−Ag, and GeS−Au films at 320 deg/RIU, 295 deg/RIU, and 260 deg/RIU, respectively, surpassing conventional SPR sensors based on Al/Ag/Au films at 111 deg/RIU, 117 deg/RIU, and 139 deg/RIU, respectively [128] . A study executed by Zhao [34] illustrates a substantial advancement in sensitivity for RI detection, achieving an optimized sensitivity of 3581.2 nm / RIU and a figure of merit of 14.37 RIU −1 .…”
Section: Plasmonic Materialsmentioning
confidence: 96%
“…[127] Sensor studies indicate the highest sensitivities for GeSÀ Al, GeSÀ Ag, and GeSÀ Au films at 320 deg/ RIU, 295 deg/RIU, and 260 deg/RIU, respectively, surpassing conventional SPR sensors based on Al/Ag/Au films at 111 deg/ RIU, 117 deg/RIU, and 139 deg/RIU, respectively. [128] A study executed by Zhao [34] illustrates a substantial advancement in sensitivity for RI detection, achieving an optimized sensitivity of 3581.2 nm/RIU and a figure of merit of 14.37 RIU À 1 . This improvement, nearly 80 % greater than conventional SPR sensors, results from covering the gold film with stable and cost-effective Germanium selenide (GeSe) nanosheets.…”
Section: Germaniummentioning
confidence: 99%
“…Similarly, At a wavelength (λ), the RI of plasmonic metal (Ag or Au) can be computed from the Drude–Lorentz model (Rahman et al 2020 , 2021 ; Panda and Pukhrambam 2021 ; Wu et al 2017 ; Jia et al 2019 , 2022 ): …”
Section: Sensor Design and Numerical Modelingmentioning
confidence: 99%
“…1. At a particular incident wavelength (𝜆) of 632.8 nm on the prism, the RI of the CaF2 prism and TiO2 adhesion layer can be calculated through the ensuing (1) and (2) as follows [52], [58]: Similarly, At a wavelength (𝜆), the RI of plasmonic metal (Ag or Au) can be computed from the Drude-Lorentz model [41], [52], [56], [59]- [61]:…”
Section: Sensor Design and Numerical Modeling 21 Design Of The Propos...mentioning
confidence: 99%